C60 additive-assisted crystallization in CH3NH3Pb0.75Sn0.25I3 perovskite solar cells with high stability and efficiency. Issue 37 (18th September 2017) - Liu, Chong; Li, Wenzhe; Li, Hongliang; Zhang, Cuiling; Fan, Jiandong; Mai, Yaohua
Abstract : The hybrid Sn–Pb perovskite solar cells with C60 additive were demonstrated to own superior stability and efficiency when exposed to the ambient environment without encapsulation. Abstract : The development of hybrid tin (Sn)–lead (Pb) perovskite solar cells likely tackles the toxic problem with the power conversion efficiency (PCE) exceeding 17%. However, the stability problems, e.g. hysteresis effect, degeneration and oxidation, appear to be the bottleneck that limit its further development. Here, we innovatively introduced C60 at the grain boundaries throughout the CH3 NH3 Pb0.75 Sn0.25 I3 (MAPb0.75 Sn0.25 I3 ) thin film, playing a role not only in in situ passivating the interfaces and reducing the pinholes of perovskite thin films, but also in preventing the penetration of moisture and oxygen from ambient atmosphere. Electrochemical impedance spectroscopy (EIS) illustrated that the recombination lifetime of both the bulk and surface of MAPb0.75 Sn0.25 I3 thin films was increased by additive incorporation of C60 . Dark I – V results for the electron/hole-only devices showed that the charge trap-state density decreased with C60 additive incorporated into the hybrid Sn–Pb perovskite thin films. Importantly, the hybrid Sn–Pb perovskite solar cells modified with C60 additive were demonstrated to have superior stability and efficiency when exposed to the ambient environment without encapsulation.